The Impact of Information on Doctors' Attitudes Toward Generic Drugs - Aggeliki V. Tsaprantzi MD; Petros Kostagiolas PhD; Charalampos Platis PhD; Vassilios P. Aggelidis PhD; Dimitris Niakas PhD (SAGE Publishing, 2016)
The objective of this study is to assess the impact of information on doctors' attitudes and perceptions toward generics. A cross-sectional survey based on a specially designed 21-item questionnaire was conducted. The survey involved doctors of different specialties working in a public hospital in Greece. The analysis includes descriptive and inferential statistics, reliability and validity tests, as well as structural equation modeling to evaluate the causal model. Statistical analysis was accomplished by using SPSS 20 and Amos 20. A total of 134 questionnaires out of 162 were received, providing a response rate of 82.71%. A number of significant associations were found between information and perceptions about generic medicines with demographic characteristics. It seems that the provision of quality information on generic drugs influences doctors' attitudes and prescription practices toward generic drugs. This is not a static process but a rather dynamic issue involving information provision policies for strengthening the proper doctors' attitudes toward generic drugs.